Investigation of Mutual Anisotropic Heisenberg Chains Which have Easy axe in Ferromagnetic with Spin S=1 by Existence of External Magnetic Field (Latakia University Journal -Basic Sciences Series, 2022)
The aim of this paper is to illustrate classic ways of studying Heisenberg  chains which describe nonlinear microscopic phenomena caused by elementary excitations in the ferromagnetics which appears as a kind of waves called spin waves (Magnons).                                                                  To study the Magnons (quantized spin waves) in ferromagnetics which spreads a certain energy according to the probable positions of the magnetic moments, the suitable wave function has been found, to find out the classic Hamiltoni and the Lagrangian then the dynamic equations to get the dispersing law and the energetic values. Then studying the effect of the external magnetic field, and single axis (easy axe) anisotropic mutual coefficient on the spreading energy of these waves, and that is according to Heisenberg’s single ion mutual anisotropic quantum model has been done.